Evaluation of Genotoxicity of Gagam-Jokyung-tang - Seong Min Hwang; Sung Young Cho; Su Yeong Kim; Jong Hyun Nho (Journal of Korean Medicine, 2026)
Objectives: This study was conducted to evaluate the genotoxic potential of Gagam-jokyung-tang.Methods: Genotoxicity was assessed using a bacterial reverse mutation test (Ames test), an in vitro mammalian chromosomal aberration test, and an in vivo micronucleus test. The bacterial reverse mutation test was performed using Salmonella typhimurium strains TA98, TA100, TA1535, and TA1537 and Escherichia coli WP2uvrA in the presence and absence of metabolic activation. The chromosomal aberration test was conducted in cultured mammalian cells under both metabolic activation and non-activation conditions. The micronucleus test was performed in ICR mice, and the frequency of micronucleated polychromatic erythrocytes in bone marrow cells was evaluated following oral administration of the test substance.Results: The test substance did not induce an increase in revertant colonies in any of the bacterial strains tested. In the chromosomal aberration test, no significant increase in structural chromosomal aberrations was observed compared with the negative control. In the micronucleus test, the frequency of micronucleated polychromatic erythrocytes was not increased in the treated groups, and no changes in the PCE/(PCE+NCE) ratio were observed.Conclusions: These results indicate that Gagam-jokyung-tang freeze-dried extract did not exhibit genotoxic potential under the conditions of the present study and may provide basic safety data for the development and safety evaluation of Gagam-jokyung-tang preparations.